Effects of elevated atmospheric carbon dioxide on the biological control of coffee leaf rust under controlled conditions - Mendes, Livia; Ghini, Raquel [UNESP]; Bettiol, Wagner (My University, 2012)
The effect of elevated atmospheric CO2 concentration on biological control of coffee leaf rust, caused by Hemileia vastatrix, was evaluated by leaf disc assay, under controlled conditions. The biocontrol agents Bacillus subtilis, Bacillus pumilus and Lecanicillium longisporum were applied 24h before, 24h after, and simultaneously with the H. vastatrix on leaf discs (diameter of 1.5cm). The CO2 concentrations tested were: 380, 430, 700 and 1300ppm for B. subtilis and B. pumilus; and 380, 430, 670 and 1200ppm for L. longisporum. The antagonists were not affected by CO2 concentrations. B. subtilis was the most effective in controlling the disease when applied before and simultaneously with pathogen.
Keywords: Climate change; Coffea arabica; Hemileia vastatrix